2009
DOI: 10.1016/j.jesp.2008.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of songs with prosocial lyrics on prosocial thoughts, affect, and behavior

Abstract: "Previous research has shown that exposure to violent media increased aggression-related affect and thoughts, physiological arousal, and aggressive behavior as well as decreased prosocial tendencies. The present research examined the hypothesis that exposure to prosocial media promotes prosocial outcomes. Three studies revealed that listening to songs with prosocial (relative to neutral) lyrics increased the accessibility of prosocial thoughts, led to more interpersonal empathy, and fostered helping behavior. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
185
2
20

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 165 publications
(224 citation statements)
references
References 33 publications
17
185
2
20
Order By: Relevance
“…Based on the present findings, and in concert with previous investigations showing positive effects of television with prosocial content (Mares & Woodard, 2005) and of songs with prosocial lyrics (Greitemeyer, 2009) …”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Based on the present findings, and in concert with previous investigations showing positive effects of television with prosocial content (Mares & Woodard, 2005) and of songs with prosocial lyrics (Greitemeyer, 2009) …”
Section: Resultssupporting
confidence: 90%
“…It may be that exposure to prosocial video games activates prosocialrelated schemas, which in turn alter the interpretation of subsequent information. In fact, Greitemeyer (2009) showed that listening to prosocial (relative to neutral) songs increased the proportion of word completions that were prosocial. This greater accessibility of prosocial thoughts may affect a video game player's interpretation of ambiguous information in that she or he is less likely to interpret cues as aggressive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But these effects may not be limited to video game exposure but also extend to other media sources. For instance, it appears that listening to songs with prosocial, relative to neutral, lyrics increases prosocial thoughts, affect, and behavior (Greitemeyer, 2009a(Greitemeyer, , 2009b. Thus, it is conceivable that prosocial music decreases the experience of schadenfreude.…”
Section: Implications Limitations and Future Researchmentioning
confidence: 99%
“…For example, Jacob et al (18) found that listening to prosocial song lyrics during the eating period in a restaurant (lunch and dinner) increased patrons' tipping behaviours, in terms of both the proportion of customers leaving a tip and the amount of money they gave per tip. Greitemeyer (2009) showed that exposure to songs with prosocial lyrics fostered prosocial tendencies by increasing prosocial thoughts, affect, and behaviour in different situations (e.g., empathy towards others in need, donations to nonprofit organizations, etc.). However lyrics music and without lyrics has a positive effect on participants' performance, the tracks with lyrics are more motivating for exercise than the same tracks without lyrics (23).…”
Section: Introductionmentioning
confidence: 99%